Synchronization, stability and normal hyperbolicity (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Synchronization is studied in the framework of invariant manifold theory. Normal hyperbolicity and its persistence are applied to give general results on synchronization and its stability. Simple numerics illustrate the importance of the stability issue.